Coarse-grain modelling using an equation-of-state many-body potential: application to fluid mixtures at high temperature and high pressure. (17th November 2018) - Larentzos, James P.; Mansell, J. Matthew; Lísal, Martin; Brennan, John K.
ABSTRACT: A many-body, coarse-grain model, termed the product gas mixture model, is presented that accurately describes the thermodynamic behaviour of molecular mixtures. The coarse-grain model is developed by first approximating the mixture as a van der Waals one-fluid, and subsequently applying an exponential-6 equation-of-state to describe the forces and energies between particles in the spirit of the many-body model pioneered by Pagonabarraga and Frenkel. Isothermal dissipative particle dynamics simulations are carried out at thermochemical states that occur during decomposition of a prototypical energetic material, RDX (1, 3, 5-trinitro-1, 3, 5-triazinane). The product gas mixture model performance is assessed by comparing to an explicit-molecule model and a hard-core coarse-grain model based on the exponential-6 pair potential. Overall, the many-body, coarse-grain model is shown to accurately capture the structural and thermodynamic properties for the wide variety of thermochemical states considered, while the hard-core coarse-grain model cannot. The many-body, coarse-grain model overcomes the issues of transferability, scaling consistency and unphysical ordered phase behaviour that often afflict coarse-grain models. While specific thermochemical conditions related to RDX decomposition are considered, the results are generally applicable to the thermodynamic behaviour of other fluid mixtures at both moderate and extreme conditions. GRAPHICAL ABSTRACT: